An ecological and hydrological evaluation of the effects of restoration on ecosystem services in the Kromme River System, South Africa - Rebelo, Alanna Jane (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScConsEcol)--Stellenbosch University, 2012.